Assessment of Competitiveness of Commercial Banks and Method of Detection Competitors in the Banking Market - Derevyanko, O.V. (Економічний вісник Донбасу, 2015)
The article is dedicated to the research of methodological and practical problems of assessing the competitiveness of banks in the banking market. It was studied methodical approach to the evaluation of the competitiveness of commercial banks, found the main shortcomings of existing banks competitiveness evaluation methods. It was developed the method of valuation of bank competitiveness through integral indicator, which allows you to get a comprehensive picture of the competitiveness of the bank, helps to identify a pre-emptive, and the critical position of the bank on individual areas of activity that is necessary for the formation of mechanism of increasing its competitiveness.